1996
DOI: 10.1104/pp.111.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Demand-Driven Control of Root ATP Sulfurylase Activity and SO42- Uptake in Intact Canola (The Role of Phloem-Translocated Glutathione)

Abstract: The activity of ATP sulfurylase extracted from roots of intact canola (Brassica napus 1. cv Drakkar) increased after withdrawal of the S source from the nutrient solution and declined after refeeding S0,'-to S-starved plants. The rate of S0,'-uptake by the roots was similarly influenced. ldentical responses were obtained in SO,'--fed roots when one-half of the root system was starved for S. S is predominantly available to higher plants as S0,'-taken up from soil by the roots. The rate of S uptake by plant root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
180
4
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(210 citation statements)
references
References 40 publications
19
180
4
3
Order By: Relevance
“…Since sulphur starvation stimulate sulphate uptake (Lass & Ullrich-Eberius, 1984 ;Clarkson & Saker, 1989 ;Hawkesford & Belcher, 1991 ;Hawkesford, Davidian & Grignon, 1993 ;Lee, 1993) and high sulphur supply leads to reduced uptake rates of sulphate (Kreuzwieser, Herschbach & Rennenberg, 1996), it appears that sulphate transport processes are well regulated. Consistent with this view Lappartient & Touraine (1996) recently proposed a demand-driven control of sulphate uptake in Canola plants.…”
Section: supporting
confidence: 59%
See 2 more Smart Citations
“…Since sulphur starvation stimulate sulphate uptake (Lass & Ullrich-Eberius, 1984 ;Clarkson & Saker, 1989 ;Hawkesford & Belcher, 1991 ;Hawkesford, Davidian & Grignon, 1993 ;Lee, 1993) and high sulphur supply leads to reduced uptake rates of sulphate (Kreuzwieser, Herschbach & Rennenberg, 1996), it appears that sulphate transport processes are well regulated. Consistent with this view Lappartient & Touraine (1996) recently proposed a demand-driven control of sulphate uptake in Canola plants.…”
Section: supporting
confidence: 59%
“…Sulphur depletion led to increased sulphate uptake and xylem loading, whereas both processes were diminished in response to a surplus of sulphate. Many studies with herbaceous plants also reported higher rates of sulphate uptake and xylem loading when the plants were starved of sulphur (Clarkson & Saker, 1989 ;Herschbach & Rennenberg, 1991 ;Lappartient & Touraine, 1996). Lappartient & Touraine (1996) interpreted these findings as a response of plants to maintain homoeostasis of sulphur in its cells.…”
Section: Influence Of Sulphur and Nitrogen Nutrition On Sulphate Tranmentioning
confidence: 99%
See 1 more Smart Citation
“…34 It has been reported that withdrawal of S from the medium leads to decreased levels of sulfate and GSH in Arabidopsis and canola plants tissues resulting in the induction of sulfate transporter systems and ATPS activity. 35,36 The inhibition in the activity of ATPS1 and APR results in the inhibition of GSH synthesis. 37,38,39 Supplementation of 0.5 mM SA results in the substantial increase in ATP sulfurylase, serine acetyl transferase activity and Cys content under salt stress and helps in reversing the effects of NaCl ¡ induced ROS on photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of ATP-sulfurylase (ATPS) was measured in leaves by the method of Lappartient and Touraine 35 . Fresh leaf tissues (1 gm) was ground at 4 C in a buffer consisting of 10 mM Na 2 EDTA, 20 mM Tris-HCl (pH 8.0), 2 mM dithiothreitol (DTT), and 0.01 g mL ¡1 PVP, using 1:4 (w/v) tissue to buffer ratio.…”
Section: Assay Of Atps Sat Contents Of S and Cysmentioning
confidence: 99%